Synthesis, spectral and thermo-kinetics explorations of Schiff-base derived metal complexes - Ahmad Naushad; Alam Manawwer; Wahab Rizwan; Ahmed Mukhtar; Ahmad Ashfaq (Open Chemistry, 2020)
Schiff-base ligand, 2,6-bis(benzimino)-4-phenyl-1,3,5-triazine (L), and its transition metal complexes of Co(ii), Ni(ii), and Cu(ii) were synthesized by refluxing the reaction mixture and its analytical, spectral, and thermogravimetric characteristics were explored by various techniques: AAS, FT-IR, UV-vis, TG-DTG, CHNS/O, and VSM. It was observed that all the metal containing complexes are non-electrolytic, mononuclear, and paramagnetic in nature, confirmed by the molar conductance and magnetic susceptibility measurements. Optical spectral data were used to investigate the geometrical and spectral parameters of [Co(L)(ac)2], [Ni(L)(ac)2], [Cu(L)(ac)2], [Cu(L)(acac)2], and [Cu(L)(fmc)2] complexes. Simultaneous thermal analyses (TG-DTG) in nitrogen atmosphere reveal that the ligand decomposes in one step, [Co(L)(ac)2], [Ni(L)(ac)2], and [Cu(L) (ac)2] complexes are decomposed in three steps, whereas [Cu(L)(acac)2] and [Cu(L) (fmc)2] are decomposed in five and two steps, respectively. In addition, activation energy (Ea) and pre-exponential factor (ln A) were evaluated by TG-DTG decomposition steps of compounds using the Coats–Redfern formula. Enthalpy (∆H), entropy (∆S), and Gibbs free energy (∆G) of the as-prepared metal complexes were also speculated by various thermodynamic equations.